2021
DOI: 10.3389/fmed.2021.687023
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Associated Factors of Flat Irregular Pigment Epithelial Detachment With Choroidal Neovascularization in Chronic Central Serous Chorioretinopathy

Abstract: Purpose: Flat irregular pigment epithelial detachment (FIPED) in chronic central serous chorioretinopathy (CSC) is strongly associated with type 1 choroidal neovascularization (CNV). The present study aimed to describe the multimodal imaging characteristics of FIPED in patients with chronic CSC and investigate the factors associated with vascularized FIPED.Methods: We included 55 chronic CSC eyes with vascularized FIPED (47 patients) and 55 chronic CSC eyes with avascular FIPED from age-matched patients (47 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Instead, the original damage of adrenalin on RPE might also play a vital role in development of CSC. 23 , 24 This idea might be of help to further clarify the original pathogenesis of CSC and the following sequence of events.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the original damage of adrenalin on RPE might also play a vital role in development of CSC. 23 , 24 This idea might be of help to further clarify the original pathogenesis of CSC and the following sequence of events.…”
Section: Discussionmentioning
confidence: 99%
“…SS-OCT and SS-OCTA have higher wavelengths and scan rates, resulting in a higher definition of images and better contrast of small neovascular structures [11]. Several studies have demonstrated that OCTA increases the detection of CNV in chronic CSC compared to conventional diagnostic modalities [3,5,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Central serous chorioretinopathy (CSC) is a vision-threatening disease characterized by increased choroidal blood flow and hyperpermeability, causing serous neurosensory retinal detachment (SRD), pigment epithelial detachment (PED), or thickened choroid 1 , 2 . In the aggravated case of recurrent episodes, prominent retinal pigment epithelium (RPE) alteration could be observed and lead to choroidal neovascularization (CNV) with persistent SRD 3 . Spaide 4 introduced the starling resistor theory, which can be explained that the structure of noncompliant outershell like brain or eye, that excessively increased blood inflow cannot enlarge vessels anymore, rather constrict the blood flow, leading to maintain suitable volume in the restricted space.…”
Section: Introductionmentioning
confidence: 99%